UPAYA PENGEMBANGAN KARAKTER ANAK MELALUI MODEL PEMBELAJARAN EXPERIENTIAL LEARNING (Efforts In Developing A Child’s Character Through An Experiential Learning Approach Model): Wahyuni Christiany Martono - Adminpintarharati (Pintar Harati: Jurnal Pendidikan dan Psikologi, 2019)
The aim of this study was to describe the efforts undertaken to develop children's character through an Experiential Learning model approach at Homy School in Palangka Raya, Central Kalimantan. This study used qualitative method. The subjects of this study were educators, children and the principals. The methodology used was collecting data by observation, interviews and documentation. The technique used to analyze data was a qualitative descriptive technique. The results showed that the implementation of Experiential Learning approach model at Homy School in Palangka Raya Central Borneo could develop children's character. Homy School implements the four stages of Experiential Learning, which are 1) concrete experiences, 2) reflective observation, 3) abstract concepts, and 4) active experiments; all these efforts are focused towards the process of developing a child's character. Positive character outputs of Experiential Learning are: a child feels they are important and able to relate themselves, to friends and the environment. They also becomes more spiritual, likeable, honest, have a sense of love, empathy, independence, responsibility, creativity, active, confident, and enjoy learning. In an effort to develop a child’s character through an Experiential Learning approach model at Homy School in Palangka Raya, Central Kalimantan, it was recommended that consistency and good collaboration continue to be maintained between the school (tutors) and parents. In addition, hoped that routine evaluations in every activity carried out.Keywords: Character Development, Experiential Learning Model Approach, Homy School Palangka Raya